Биохимические показатели состояния печени крыс, получавших высокожировые рационы - Васюк, В.Л.; Гоженко, А.И.; Левицкий, А.П. (Актуальні проблеми транспортної медицини, 2015)
Кормление крыс высокожировыми рационами (ВЖР), содержащими подсолнечное, оливковое, пальмовое или сливочное масло в количестве 15 % к массе комбикорма, вызывает увеличение живой массы (более выраженное для пальмового масла), повышение в печени уровня маркеров воспаления и снижение активности лизоцима, более выраженные для пальмового и сливочного масел. В сыворотке крови увеличивается содержание глюкозы и холестерина, а также активность эластазы (для пальмового масла). По-видимому, более патогенное действие ВЖР, содержащих пальмовое или сливочное масло, зависит от высокого уровня в них пальмитиновой кислоты. Годівля щурів високожировими раціонами (ВЖР) з вмістом соняшникової, оливкової, пальмової олії або вершкового масла в кількості 15 % від маси комбікорму викликає підвищення живої маси (більш виражене для пальмової олії), зростання в печінці рівня маркерів запалення та зниження активності лізоцима, в більшій мірі для пальмової олії та вершкового масла. В сироватці крові підвищується вміст глюкози і холестерину, а також активність еластази (для пальмової олії). Вирогідно, що патогенна дія ВЖР з вмістом пальмової олії і вершкового масла залежить від високого рівня в них пальмітинової кислоти. Aim: To determine the liver condition of rats fed with fats of different fatty acid compositions.
Materials and methods: We used the following dietary fats: refined sunflower oil, refined olive oil, palm oil, milk fat (butter). Feeding of rats was carried out for 41 days using 15 % of the studied oils in the food. The liver condition was evaluated by biochemical markers of liver (elastase, MDA, alkaline phosphatase (ALP), lysozyme, catalase) and blood serum markers (glucose, cholesterol, elastase, ALT, ALP).
Results: The increase in the weight gain was more pronounced when feeding with palm oil; the increase of inflammatory markers levels (MDA and elastase) was greater when feeding with palm oil and butter. Conversely, the lysozyme activity in the liver was significantly reduced at fat feeding, particularly for palm oil and butter. In the serum of all animals fed with fat there was the significant increase of glucose and cholesterol levels, as well as the increase of the elastase activity (after palm oil).
Conclusion: A high-fat diet causes the development of an initial phase of inflammatory and degenerative processes in liver, which is more pronounced for fats high in palmitinic acid (palm oil and butter).